Thomas Adès, Concerto for Piano and Orchestra. Analysis, Pattern and Form of the First Movement (Ex Chordis, 2024)
This paper will explore the first movement of Thomas Adès’ Concerto for Piano and Orchestra [2018], focusing on its harmonic, structural, and melodic components. The analysis will examine the unconventional treatment of harmonic patterns, including the circle of fifths, chromaticism, and the use of the (025) pitch class set. Additionally, the sonata form will be discussed, highlighting how Adès integrates and manipulates traditional elements within this framework. The study will also investigate Adès’ use of melodic sequences, particularly those based on intervals of the fifth and fourth, showing how they evolve throughout the movement. The overall goal is to demonstrate how Adès blends traditional techniques with modern innovation, creating a distinctive compositional style.
Keywords: Thomas Adès; Music Analysis; Orchestra; Contemporary; Artistic Research